Study and emulation of IPv6 Internet-exchange-based addressing models. - Fernandez, D. (IEEE Communications magazine)
This article presents the first results of our study and experimentation with the new IPv6 IX-based address assignment model and its deployment in IXs where peering is organized around route servers. An IX model that identifies where the new IX customers can be located and how services like provider choice or multihoming can be offered is proposed. The article also describes the emulation environment that has been developed to easily create and experiment with complex IX scenarios without involving setup of costly configurations made of several pieces of equipment. This work has been carried out in the context of the European Union funded project Euro6IX.